A retrospective study of transfusion practices in a Tertiary Care Institute - Babita Raghuwanshi; N K Pehlajani; Mithilesh K Sinha; Swagata Tripathy (Indian Journal of Anaesthesia, 2017)
Background and Aims: Excessive requests for cross matching blood which is more than the blood required for transfusion are usually based on worst case assumptions leading to overestimation of blood usage. We investigated the blood ordering pattern and transfusion practices so as to incorporate a blood ordering schedule for streamlining the use of blood in various hospital departments. Methods: The study was conducted over a period of 19 months in a 350 bedded tertiary teaching hospital. Source of data was blood bank requisition forms and blood bank registers of patients who underwent elective or emergency procedures in the hospital, for which blood was ordered. Data were entered in MS Excel and analysed using SPSS version 20. Results: The blood bank was requested to prepare 10,594 units of blood for 2556 patients. The blood utilised was 16.04% of total cross matched blood, leaving 83.9% of units cross matched but not transfused to patient for whom it was prepared, i.e., wasted. The surgery department had the highest number of units cross matched and transfused. The least number of units cross matched and wasted due to non-transfusion were from the Department of Oncology. Conclusion: The current deficiency of explicit maximum blood order schedule in our hospital is the major factor responsible for high cross match: transfusion ratio. Therefore, a maximal surgical blood order schedule has been suggested to the hospital transfusion committee to implement maximum surgical blood order schedules for selected procedures.